Actividades creativas y desarrollo económico en Portugal: Un análisis territorial - Figueira, Jorge (2013)
The creative economy has been the subject of increasing interest in recent years, both in the area of cultural economics as well as in economic development studies and the analysis of spatial disparities. The underlying notion is to consider creative capital as a production factor linked to talent, technological innovation and initiative, which may shape part of an area or region’s economic flows, replacing merely physical production factors. Based on these considerations, the current work seeks to explore the territorial distribution of creative activities in Portugal and to ascertain the relationship with the level of economic development. This involves defining the creative activities sector and its determinant components, for which purpose we draw on R. Florida’s (2002) widely embraced factors; talent, technology, and tolerance.